Supramolecular polyelectrolyte hydrogel based on conjoined double-networks for multifunctional applications. Issue 44 (13th October 2022) - Yang, Wen Jing; Zhang, Rui; Guo, Xian; Ma, Ruixiang; Liu, Zhiyuan; Wang, Ting; Wang, Lianhui
Abstract : A supramolecular polyelectrolyte PVA-PAANa-PAH hydrogel with excellent mechanical properties and superior conductive stability has been fabricated for multifunctional applications. Abstract : Recently, the skin-biomimetic ionic conductive hydrogels have emerged as a competitive alternative in soft electronics applications due to their excellent ionic conductivity and good biocompatibility. One common approach for preparation of the ionic conductive hydrogels is adding external salts into the single- and double-network hydrogels. However, these ionic hydrogels usually exhibit low mechanical strength and/or poor conductive stability, constraining their further applications. Herein, a supramolecular polyelectrolyte PVA-PAANa-PAH hydrogel based on conjoined double-networks (DN) stabilized by multiple physical interactions has been fabricated. Owing to the unique network structures, the hydrogel exhibits excellent mechanical properties (fracture strain: 768% and toughness: 2.25 MJ m −3 ) and recovery capabilities (recovery ratio of maximum stress: 90.5%). Due to the presence of internal ions provided by polyelectrolytes, the PVA-PAANa-PAH hydrogel shows good ionic conductivity, high sensitivity (pressure sensitivity: 0.246 kPa −1 within the range of 0–10 kPa) and conductive stability in detecting pressure and various deformations. Accordingly, the corresponding hydrogel sensor can not only be applied in human movement monitoring, handwriting recognition and water droplet falling sensing successfully, but also in underwater movement detection. Notably, the hydrogel can also work as a wearable sensor for real-time detection of electrophysiological signals such as ECG signals. Lastly, the unique humidity-adjustable transparency enables the hydrogel to be applied in information encryption and decryption. The prepared supramolecular polyelectrolyte hydrogel provides a promising strategy to fabricate ionic conductive hydrogel with good mechanical properties and excellent conductive stability for multifunctional applications.